Investigations on different distribution systems for dusts inside the 20L-sphere - Spitzer, Stefan H; Pandal, Adrian; Rodriguez, Manuel Velasco; Schmidt, Martin; Danzi, Enrico; Dufaud, Olivier; Janovský, Břetislav (Elsevier Science BV, 2024)
The determination of several safety characteristics for dusts requires the dispersion of it in air. This is normally conducted using two vessels, one with an overpressure holding the dust and dispersing it into the second one, where the explosion takes place, through a nozzle. This procedure has the disadvantage that some dusts cannot be conveyed through the nozzle properly. Another disadvantage is that the pressure balancing between the two vessels depends on the dust loading and especially for heavy dusts and high loadings the initial pressure inside the explosion vessel might be reduced. Flocky dusts or dusts that might be dangerous to convey through a thin nozzle with an overpressure (nanopowders, zirconium) are also difficult to test according to the extisting standards andmay not be tested with the standard nozzles, that are so far used for the determination of safety characteristics. One very recent example, testing nitrocellulose, raised the question, whether some dusts even pose a risk being distributed and pressed through a nozzle for the testing device and, in worst case, for the operator. Previous researchers have developed alternative types of nozzles for specific types of dust, but provide limited evaluation of their performance relative to standard nozzles. Additionally researchers have not provided sufficient geometry so that they can be reproduced by others. One alternative nozzle for the dispersion of flocky or coarse dusts is stated in the ISO standard but not described there either. This article investigates four types of nozzles: The two standard ones that are widely used already, an alternative type, that got introduced into the international standard in 2016 but is still seldomly used and one that was constructed to overcome some of the observed disadvantages. The injection curves are compared with and without dust loadings as well as the explosion characteristics. Eventually, a suggestion is given for different types of dusts.
Výzkum různých rozviřovacích systémů prachu ve 20L kouli
Keywords: Safety characteristics; Turbulence; Dust explosions; Nozzles; Distribution; Bezpečnostní charakteristiky; Turbulence; Výbuchy prachů; Trysky; Rozvíření